How anticipated positive and negative emotions influence pro-environmental behavior via environmental attitudes - Niu, Xueting; Li, Menghan; Sun, Zhenhe; Li, He (Frontiers in Psychology, 2025)
BackgroundAnticipated emotions are important predictors of pro-environmental behavior within the extended theory of planned behavior. However, their mechanisms need further exploration through emotion theories. This study applies Affective Events Theory (AET), a framework originally developed to explain emotional influences on behavior in workplace settings and more recently extended to the context of pro-environmental behavior, to examine how anticipated positive and negative emotions influence pro-environmental behavior, with environmental attitudes serving as a mediator.MethodsA cross-sectional survey was conducted to measure anticipated positive and negative emotions, environmental attitudes, pro-environmental behavior, and demographic variables. A total of 500 questionnaires were randomly distributed via the Credamo online platform, yielding 442 valid responses.Results and conclusionBoth anticipated positive and negative emotions positively influence pro-environmental behavior, with environmental attitudes mediating these effects. Specifically, anticipated positive emotions not only exert a direct impact on pro-environmental behavior but also indirectly influence it through environmental attitudes. In contrast, anticipated negative emotions affect pro-environmental behavior exclusively through the mediating role of environmental attitudes. The direct effect of anticipated positive emotions may reflect the approach-oriented motivational function of positive emotions. Meanwhile, the indirect effects of both types of emotions through environmental attitudes suggest that anticipated emotions promote pro-environmental behavior by influencing individuals’ perceptions of the human–environment relationship. These findings significantly advance our understanding of the emotional mechanisms underlying pro-environmental behavior and offer valuable implications for designing emotion-based interventions aimed at fostering environmentally responsible actions.